Pengaruh variasi temperatur dan holding time pada proses annealing leaf spring dumb truck bekas terhadap nilai kekerasan - Eko Nugroho; Nurlaila Rajabiah; Tri Cahyo Wahyudi; Juda Inai (Universitas Muhammadiyah Metro, 2023)
Leaf spring is a flat plate component that is clamped together to obtain product efficiency using metal materials, sometimes requiring high hardness and wear resistance. The steel working process is highly dependent on the heat treatment process and the cooling media used to obtain good product quality. The purpose of this study was to determine the effect of variations in temperature and holding time in the process of annealing used leaf springs and trucks on hardness values. This test has been carried out with each variation, namely, temperature 450oC, 550oC, 650oC and held for 30, 60, and 90 minutes as well as the cooling process using air in the heating furnace room. Based on the data obtained, the influence of temperature media and holding time in the Annealing process of used leaf spring dumb trucks has a low hardness value at a temperature of 650°C with a holding time of 30 minutes, 60 minutes and 90 minutes, the lowest hardness value is at 90 minutes, namely 7.7 While the HRC temperature of 550°C and holding time of 90 minutes reaches 26.9HRC, the hardness value is higher and the same as 450°C with holding time of 90 minutes which reaches 30.8HRC. The influence of temperature and holding time on the annealing process of used leaf spring dumb trucks has the lowest hardness value at a temperature of 650°C with a holding time of 90 minutes, namely 7.7 HRC.